Disfunción familiar y su influencia en la conducta desadaptativa de un estudiante - Velarde Macias, Lilibeth Jacqueline (2020)
This case study covers a problem that is currently occurring in the educational unit “FAUSTO MISAEL OLALLA GAIBOR”, having as objetive describe the incidence of dysfunctional family in maladaptive behavior of a 12-year-old teenager.For the elaboration of this case study was used various strategies for information gathering dare the clinical history, psychometric test, and interviews, the diagnosis was obtained. And in turn verify that family dysfunction yes intervenes significantly in the proper development of the patient